2013
DOI: 10.4103/2141-9248.113653
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of women towards breast cancer in Benin City, Nigeria

Abstract: Background:Breast cancer is the principal cause of cancer deaths among women worldwide. African women in comparison with their low incidence of cancer, disproportionately bear a high cancer mortality rate.Aim:The study was aimed at investigating level of breast cancer awareness, attitudes and practices towards early detection strategies.Subjects and Methods:The study was conducted in Oredo municipal council of Benin city and adopted a descriptive cross sectional design. Purposive, stratified and simple random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 15 publications
15
60
0
Order By: Relevance
“…The results are supported by the findings of [14] that 90.5 percent of women knew about breast cancer and 65.2 percent could identify up to two breast cancer signs and symptoms. Contradictory to the findings, [15] found that only one-half of the women were aware of breast cancer and women in high risk group had poor knowledge of the risk factors for breast cancer [16].…”
Section: Results Andsupporting
confidence: 80%
“…The results are supported by the findings of [14] that 90.5 percent of women knew about breast cancer and 65.2 percent could identify up to two breast cancer signs and symptoms. Contradictory to the findings, [15] found that only one-half of the women were aware of breast cancer and women in high risk group had poor knowledge of the risk factors for breast cancer [16].…”
Section: Results Andsupporting
confidence: 80%
“…28 Most women in our study had heard about BC, but only a few had good knowledge of its causes or symptoms, in line with the findings reported by other Nigerian studies. 29,30 Women in our study who did not practice BSE had higher odds of presenting later than women who did. Other authors have reported an association between education and practice of BSE.…”
Section: Discussionmentioning
confidence: 58%
“…In studies from different countries, the rate of mammography within two years ranged from 43% to 78% (26)(27)(28)33,34). Studies in Turkey focused on whether mammography was obtained or not, rather than the timing of mammography (16,17,19,20,29,32,).…”
Section: Resultsmentioning
confidence: 99%